Oman Beyond the Oil Horizon : Policies Toward Sustainable Growth - Treichel, Volker (Occasional Papers; Occasional Paper ;, 1999)
With the steady increase of crude oil production and the surge in oil prices in the mid- and late 1970s, Oman embarked upon an economic development path that transformed it into a prosperous country. Today Oman boasts impressive physical infrastructure, much improved socioeconomic conditions, and a high standard of living. The purpose of this background study is to contribute to a better understanding of developments in the Omani economy since 1980 and of the policy challenges the government faces in the medium term. The study focuses on some central aspects of Oman's economic experience, including the potential structural impediments to growth.